216 - ANALYSIS OF VOCATIONAL TRAINING IN CIRCUS: A DIALOGUE WITH THE ARTIST (Fiep Bulletin - online, 2011)
This study was qualitative and quantitative research, in the view of circus performers, the main factors that influence the practice and stay in the circus activity in circuses today, highlighting the academic training that these guys are / were affected. A semistructured interview was administered to a sample consisting of 20 artists that make circus circus midsize northwestern state of Paraná and the data collected was analyzed descriptively by using the technique of thematic content analysis. The results show that the life of circus artists have started around 5 or 6 years old, one of the main reasons for entering this environment is the family ties and leave the circus, would seek a means of livelihood activities related to those performed in part circus. We conclude that the art of the circus that has fascinated the spectators should be understood as denoting a profession of excessive physical and mental sacrifice in pursuit of the need to achieve a desired level of high performance, yet this "sacrifice" comes spontaneously, since currently the family bond is still the main reason for the initiation of circus artists in the middle. It is also emphasized the importance given by the circus artists in the process of constructing knowledge about the skills implicit in every issue during his circus training and seeks to increase the access of this knowledge to the general public. Thus, we believe that the circus must be treated for physical education as a knowledge on the culture body to be working with our students, so that we can promote understanding, appreciation and appropriation of artistic expression is through an approach that also allows every student, the discovery of his physical and expressive possibilities.
Keywords: circus; training; leisure activities